Semiotic Analysis of a Public Service Advertising I compost food waste - Muhammad Rudi Kurniawan; Sahrul N; Syafwandi Syafwandi (Jurnal Desain Komunikasi Visual Nirmana, 2019)
Most of the current researches on analyzing public service advertisings (PSA) about food waste into compost is concentrated on the interconnection between environmental, economic, and social aspects. This study has considered the semiotic analysis of the selected PSA through Barthes’ The Five Codes theory. Using the semiotic framework, the paper explains the messages of the PSA “I Compost Food Waste” and describes how this advertising provides insight into design innovation. The findings have shown that the PSA combined with the semiotics is capable of raising people’s awareness about food waste into compost.